The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41598-019-57373-z
|View full text |Cite
|
Sign up to set email alerts
|

Maternal preconception lipid profile and gestational lipid changes in relation to birthweight outcomes

Abstract: In 575 women with 1–2 prior pregnancy losses; total cholesterol, low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and triglycerides (TG) were evaluated preconception and throughout pregnancy to evaluate whether previously observed associations between third trimester maternal lipid profile and birthweight outcomes are driven by preconception lipids or lipid changes during pregnancy. Lipid trajectories were compared by pre-pregnancy body mass index (BMI) <25 or ≥25 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…The increase in HDL was associated with decreased BW z-score in women with GDM [3]. However, Bever et al [33] found that the increase in HDL-c concentration from prepregnancy to gestational week 28 was associated with a decreased risk of SGA in the BMI ≥ 25 kg/m 2 group. This study aimed to evaluate the associations between exposure and outcomes in all participants and the models including liner and logistic regression had been adjusted for pre-BMI.…”
Section: Discussionmentioning
confidence: 93%
“…The increase in HDL was associated with decreased BW z-score in women with GDM [3]. However, Bever et al [33] found that the increase in HDL-c concentration from prepregnancy to gestational week 28 was associated with a decreased risk of SGA in the BMI ≥ 25 kg/m 2 group. This study aimed to evaluate the associations between exposure and outcomes in all participants and the models including liner and logistic regression had been adjusted for pre-BMI.…”
Section: Discussionmentioning
confidence: 93%
“…HDL-c, as a protective factor for vascular endothelial cells, plays a vital role in protecting the cardiovascular system of pregnant women during pregnancy [16]. This may indicate that relatively higher levels of maternal HDL-c are associated with a reduced risk of SGA, which could be demonstrated by Bever et al [20]. However, our nding regarding the association between the levels of maternal HDL-c and SGA seemed to be a little counterintuitive.…”
Section: Discussionmentioning
confidence: 75%
“…On the one hand, elevated maternal HDL-c has vasodilatory, antioxidant, antithrombotic and anti-in ammatory effects in protecting against endothelial cell damage during pregnancy [16]. This anti-in ammatory effect is helpful to reduce the risk of PTB, which could be demonstrated in a recent systematic review [17].On the other hand, maternal elevated HDL-c has an important effect on promoting foetal growth and development [18] and reduces the risk of low birth weight [19] and SGA [20]. However, a systematic review found that the risk of PTB was not affected by HDL-c [21].…”
Section: Introductionmentioning
confidence: 99%
“…We only had information on maternal biomarker characteristics available from non-fasting samples in the first half of pregnancy. Previous studies have shown that maternal early-pregnancy biomarkers at least partly reflect maternal biomarkers in the preconception period [ 37 , 38 ]. However, to enable use of the full model already before pregnancy and in earlier stages of pregnancy, further studies are needed to replicate findings using maternal biomarker characteristics already obtained prior or in earlier stages of pregnancy.…”
Section: Discussionmentioning
confidence: 99%